A new species of Buprestis Linnaeus, 1758 from Veracruz, Mexico (Coleoptera: Buprestidae: Buprestini) and a brief discussion of the Mesoamerican species of the subgenus Knulliobuprestis Kurosawa, 1988 - Bellamy, C. L. (Zootaxa, 2011)
A new species, Buprestis (Knulliobuprestis) aurora, is described from localities in the Mexican state of Veracruz and discussed in relation to B. catoxantha Gory, 1840. The following species of Buprestis are transferred to the subgenus Knulliobuprestis: B. bergevini Théry 1911, B. carabuho Westcott 1998, B. catoxantha Gory 1840 (synonyms: B. jimenezi Dugès 1891 and B. variegata Laporte & Gory 1837), B. hauseri Obenberger 1928, and B. panamensis Théry 1923 (synonym: B. panamensis var. nigripennis Théry 1934).